Outcomes of abandoned radical hysterectomy in patients with stages IB-IIA cervical cancer found to have positive nodes during the operation - Suprasert P. (2014)
The objective of this study was to evaluate the outcomes of stages IB-IIA cervical cancer patients whose radical hysterectomy (RH) was abandoned for positive pelvic nodes detected during the operation compared with those found to have positive nodes after the operation. Among 242 patients with planned RH and pelvic lymphadenectomy (RHPL) for stages IB-IIA cervical cancer, 23 (9.5%) had grossly positive nodes. RH was abandoned, and complete pelvic lymphadenectomy was performed. Of these 23 patients, 22 received adjuvant chemoradiation, and the remaining 1 received adjuvant radiation. Four patients with positive para-aortic nodes were additionally treated with extended-field irradiation. When compared with 35 patients whose positive nodes were detected after the operation, there were significant differences regarding number of positive nodes and number of patients receiving extended-field irradiation. Complications in both groups were not significantly different, but the 2-year disease-free survival was significantly lower in the abandoned RH group compared with that of the RHPL group (58.5% versus 93.5%, P = 0.01). In conclusion, the survival of stages IB-IIA cervical cancer patients whose RH was abandoned for grossly positive pelvic nodes was significantly worse than that of patients whose node metastasis was identified after the operation. This is because the abandoned RH group had worse prognostic factors. © 2005 IGCS.